The PI3-kinase/mTOR-targeting drug NVP-BEZ235 inhibits growth and IgE-dependent activation of human mast cells and basophils. - Katharina Blatt; Harald Herrmann; Irina Mirkina; Emir Hadzijusufovic; Barbara Peter; Sabine Strommer; Gregor Hoermann; Matthias Mayerhofer; Konrad Hoetzenecker; Walter Klepetko; Viviane Ghanim; Katharina Marth; et al. (PLoS ONE)
The phosphoinositide 3-kinase (PI3-kinase) and the mammalian target of rapamycin (mTOR) are two major signaling molecules involved in growth and activation of mast cells (MC) and basophils (BA). We examined the effects of the dual PI3-kinase/mTOR blocker NVP-BEZ235 on growth of normal and neoplastic BA and MC as well as immunoglobulin E (IgE)-dependent cell activation. Growth of MC and BA were determined by measuring (3)H-thymidine uptake and apoptosis. Cell activation was determined in histamine release experiments and by measuring upregulation of CD63 and CD203c after challenging with IgE plus anti-IgE or allergen. We found that NVP-BEZ235 exerts profound inhibitory effects on growth of primary and cloned neoplastic MC. In the MC leukemia cell line HMC-1, NVP-BEZ235 showed similar IC(50) values in the HMC-1.1 subclone lacking KIT D816V (0.025 µM) and the HMC-1.2 subclone expressing KIT D816V (0.005 µM). Moreover, NVP-BEZ235 was found to exert strong growth-inhibitory effects on neoplastic MC in a xenotransplant-mouse model employing NMR1-Foxn1(nu) mice. NVP-BEZ235 also exerted inhibitory effects on cytokine-dependent differentiation of normal BA and MC, but did not induce growth inhibition or apoptosis in mature MC or normal bone marrow cells. Finally, NVP-BEZ235 was found to inhibit IgE-dependent histamine release in BA and MC (IC(50) 0.5-1 µM) as well as anti-IgE-induced upregulation of CD203c in BA and IgE-dependent upregulation of CD63 in MC. In summary, NVP-BEZ235 produces growth-inhibitory effects in immature neoplastic MC and inhibits IgE-dependent activation of mature BA and MC. Whether these potentially beneficial drug effects have clinical implications is currently under investigation.